Editorial (Condensed Matter Physics, 2009)
This issue of “Condensed Matter Physics” is dedicated to the 100th anniversary of an outstanding personality of the XXth century, physicist and mathematician Mykola Bogolyubov (21.08.1909–13.02.1992).